2022
DOI: 10.3389/fendo.2022.810914
|View full text |Cite
|
Sign up to set email alerts
|

Metformin Use in Relation to Clinical Outcomes and Hyperinflammatory Syndrome Among COVID-19 Patients With Type 2 Diabetes: A Propensity Score Analysis of a Territory-Wide Cohort

Abstract: AimThis study was conducted in order to evaluate the association between metformin use and clinical outcomes in type 2 diabetes mellitus (T2DM) patients hospitalized with coronavirus disease 2019 (COVID-19).MethodsPatients with T2DM with confirmed diagnosis of COVID-19 and admitted between January 21, 2020, and January 31, 2021 in Hong Kong were identified in our cohort. Exposure was defined as metformin use within 90 days prior to admission until hospital discharge for COVID-19. Primary outcome was defined as… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
2
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 37 publications
1
2
0
Order By: Relevance
“…Several retrospective cohort studies have demonstrated low mortality in patients receiving metformin. 15 17 24 25 In line with our findings, other meta-analysis have revealed a significantly lower mortality in patients receiving metformin. 7 26 Retrospective cohort studies have shown metformin use to be an independent factor associated with mortality.…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…Several retrospective cohort studies have demonstrated low mortality in patients receiving metformin. 15 17 24 25 In line with our findings, other meta-analysis have revealed a significantly lower mortality in patients receiving metformin. 7 26 Retrospective cohort studies have shown metformin use to be an independent factor associated with mortality.…”
Section: Discussionsupporting
confidence: 92%
“…1 Several studies have demonstrated high mortality rate in type 2 diabetes mellitus patients 1,5,6,24 ; however, the effect of antidiabetics on the mortality remains to be elucidated. 25 Thus, the present meta-analysis was conducted to assess the association of metformin use with mortality in COVID-19 patients. The present meta-analysis was based on data from nine studies on COVID-19 patients.…”
Section: Discussionmentioning
confidence: 99%
“…Regarding the use of oral antidiabetic agents, metformin should be stopped at admission but if and when the risk of lactic acidosis is considered low, it should be restarted since it appears to improve the outcome of COVID-19[ 12 , 15 , 16 ]. If used, the dose of metformin should be reduced in patients with estimated glomerular filtration rate (eGFR) between 30 and 45 mL/min and should be discontinued in patients with eGFR < 30 mL/min, liver failure, high risk for lactic acidosis and before iodine contrast imaging[ 17 ].…”
Section: Antidiabetic Treatmentmentioning
confidence: 99%